Outcomes of 1, 639 hepatectomies for non‐colorectal non‐neuroendocrine liver metastases: a multicenter analysis. (20th November 2018) - Sano, Keiji; Yamamoto, Masakazu; Mimura, Tetsushige; Endo, Itaru; Nakamori, Shoji; Konishi, Masaru; Miyazaki, Masaru; Wakai, Toshifumi; Nagino, Masato; Kubota, Keiichi; Unno, Michiaki; Sata, Naohiro; et al.
Abstract: Background: Whether non‐colorectal non‐neuroendocrine liver metastasis (NCNNLM) should be treated surgically remains unclear. Methods: Data regarding 1, 639 hepatectomies performed between 2001 and 2010 for 1, 539 patients with NCNNLM were collected from 124 institutions. Patient characteristics, types of primary tumor, characteristics of liver metastases, and post‐hepatectomy outcomes were analyzed. Results: The five most frequent primary tumors were gastric carcinoma (540 patients [35%]), gastrointestinal stromal tumor (204 patients [13%]), biliary carcinoma (150 patients [10%]), ovarian cancer (107 patients [7%]), and pancreatic carcinoma (77 patients [5%]). R0/1 hepatectomy was achieved in 90% of patients, with 1.5% in‐hospital mortality rate. Overall and disease‐free survival rates of 1, 465 patients included in survival analysis were 41% and 21%, respectively, at 5 years, and 28% and 15%, respectively, at 10 years. Five‐year survival associated with the five frequent primary tumors were 32%, 72%, 17%, 52%, and 31%, respectively, and factors predictive of a poor outcome differed by the primary tumor type. Conclusions: Our data indicated that hepatectomy is safe for NCNNLM and that patient prognoses vary depending on the type of primary tumors. Indications for hepatectomy should be determined with reference to survival rates and risk factors specific to each of the various types of primary tumor. Abstract : Highlight On behalf of the Japanese Society of Hepato‐Biliary‐Pancreatic Surgery, Sano and colleagues analyzed 1, 639 patients, the largest cohort ever, with non‐colorectal, non‐neuroendocrine liver metastases surgically resected between 2001 and 2010. The surgical outcomes were independently analyzed and found to be specific to each of the various types of primary tumor.